Gender-based differences in psychological distress in the academic environment - Tri Windi Oktara; Farhanah Murniasih; Hilda Rosida; Vasco Delano; Lusinta Rehna Ginting; Qoulan Sadidah (Jurnal Konseling dan Pendidikan, 2026)
Mental health problems among university students have become a growing concern worldwide due to their impact on academic performance and well-being. Although psychological distress among students has been widely studied, findings regarding gender differences remain inconsistent across cultural contexts, particularly in Indonesia. Therefore, this study aimed to examine differences in psychological distress between male and female university students. A quantitative approach was employed involving 353 students selected through accidental sampling. The Rasch Model was used to transform ordinal responses into interval-level measures of psychological distress, while Welch’s t-test was applied to compare groups because of unequal sample sizes between male and female participants. The findings revealed that female students demonstrated higher psychological distress scores (M = -0.94 logits) than male students (M = -1.32 logits), indicating greater psychological distress among female participants. Welch’s t-test showed a statistically significant gender difference in psychological distress (p = .001). These findings suggest that female students may be more vulnerable to psychological distress within academic environments. The study highlights the importance of incorporating gender considerations into student mental health services and developing targeted support programs within higher education institutions.